2008
DOI: 10.1007/s11269-008-9291-3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Artificial Neural Network Techniques for Municipal Water Consumption Modeling

Abstract: Various Artificial Neural Network techniques such as Generalized Regression Neural Networks (GRNN), Feed Forward Neural Networks (FFNN) and Radial Basis Neural Networks (RBNN) have been evaluated based on their performance in forecasting monthly water consumptions from several socio-economic and climatic factors, which affect water use. The data set including total 108 data records is divided into two subsets, training and testing. The models consisting of the combination of the independent variables are const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
33
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(33 citation statements)
references
References 25 publications
0
33
0
Order By: Relevance
“…temperature and rainfall (Adamowski 2008;Zhang et al 2006;Jain et al 2001; among others), relative humidity, wind speed, and dew point (Zhang et al 2006). For the medium/long-term prediction, apart from historical water demand, the use of diverse variables such as household income (Chang and Makkeasorn 2006;Lui et al 2003), population and land use (Chang and Makkeasorn 2006), water price (Firat et al 2009;Lui et al 2003) and inflation rate (Firat et al 2009) have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…temperature and rainfall (Adamowski 2008;Zhang et al 2006;Jain et al 2001; among others), relative humidity, wind speed, and dew point (Zhang et al 2006). For the medium/long-term prediction, apart from historical water demand, the use of diverse variables such as household income (Chang and Makkeasorn 2006;Lui et al 2003), population and land use (Chang and Makkeasorn 2006), water price (Firat et al 2009;Lui et al 2003) and inflation rate (Firat et al 2009) have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, the water demand modelling is a very important tool for planning and management water resources because provides adequate understanding of this behavioural response to changes in price (Firat et al 2009). For urban water, the accurate characterization of demand needs take into account that different types of users are connected to the public water network: residential, service and industrial.…”
Section: Introductionmentioning
confidence: 99%
“…The weights are adjusted based on a comparison of ANN output and the target until they match. Some of the recent applications include synthetic streamflow generation (Ahmed and Sarma 2009), municipal water consumption modeling (Firat et al 2009), identification of unknown pollution sources in groundwater (Singh and Datta 2007), flood management (Ahmad and Simonovic 2006), and sediment loss prediction (Sarangi and Bhattacharya 2005). ANNs have an advantage over deterministic models in respect of the data needs that are less and well suited for long-term forecasting (Sarangi et al 2006).…”
mentioning
confidence: 99%